Changes in phosphorus fractions caused by increased microbial activity in forest soil in a short-term incubation study. Issue 1 (1st January 2018) - Kunito, Takashi; Hiruta, Naomi; Miyagishi, Yasunori; Sumi, Hirotaka; Moro, Hitoshi
Abstract: The effects of adding larch ( Larix kaempferi ) leaf litter and nitrogen (N) on microbial activity and phosphorus (P) fractions in forest soil were examined in a short-term (28-d) laboratory incubation study. The soil was analyzed using a modified Hedley sequential extraction procedure and an acid phosphatase assay. The addition of larch litter and N increased the acid phosphatase activity and decreased the labile P (H2 O-P + NaHCO3 -P) concentration. Compared with addition of larch litter only, addition of both inputs decreased the proportion of inorganic P (Pi) and increased that of organic P (Po) in the NaOH fraction, bound to aluminum and iron oxides. The results of nutrient (carbon, N, or P) addition indicated that acid phosphatase was synthesized to acquire P. This study suggests that, in this forest soil, P in the H2 O-P + NaHCO3 -P and in the NaOH-Pi fractions was available for soil microorganisms to decompose leaf litter and that increase in microbial activity eventually translated in an increase in the proportion of Po found in the NaOH fraction in this forest soil.